1997
DOI: 10.1086/304132
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Properties of Early‐Type Galaxies as Observed withASCA

Abstract: We have systematically investigated the Advanced Satellite for Cosmology and Astrophysics (ASCA) spectra of 12 early-type galaxies. This paper presents the global spectral properties of these systems based on a larger sample than in any previous ASCA study. The X-ray spectra were uniformly Ðtted by a two-component model consisting of hard X-rays from thermal emission with a temperature of about 10 keV or from a power law with index 1.8, plus soft X-rays from a thin thermal plasma with temperature ranging from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
165
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(196 citation statements)
references
References 31 publications
27
165
4
Order By: Relevance
“…which was first derived with Einstein (e.g., Forman et al 1985;Canizares et al 1987) and then updated using Ginga and ASCA (Makishima et al 1989;Matsushita et al 1994;Reynolds et al 1997;Matsumoto et al 1997). Since the correlation is thought to represent the dominant contribution of neutron star binaries to , we infer that the hard component of NGC hard L X 1316 is also dominated by the integrated emission from neutron star binaries, with little room for the LLAGN contribution.…”
Section: ϫ16mentioning
confidence: 92%
See 1 more Smart Citation
“…which was first derived with Einstein (e.g., Forman et al 1985;Canizares et al 1987) and then updated using Ginga and ASCA (Makishima et al 1989;Matsushita et al 1994;Reynolds et al 1997;Matsumoto et al 1997). Since the correlation is thought to represent the dominant contribution of neutron star binaries to , we infer that the hard component of NGC hard L X 1316 is also dominated by the integrated emission from neutron star binaries, with little room for the LLAGN contribution.…”
Section: ϫ16mentioning
confidence: 92%
“…Both these components are characteristic of elliptical galaxies, among which the former can be identified with the thermal emission from hot interstellar medium (ISM; e.g., Forman, Jones, & Tucker 1985;Canizares, Fabbiano, & Trinchieri 1987;Awaki et al 1994). The hard component is basically interpreted as integrated hard X-rays from neutron star binaries (e.g., Makishima et al 1989;Matsushita et al 1994;Matsumoto et al 1997) but may be partially contributed by the active nucleus, because AGN emission and the integrated X-ray binary emission often exhibit similar spectral shapes in the ASCA energy band.…”
Section: ϫ16mentioning
confidence: 99%
“…The X-ray halo luminosity of NGC 6251 is two orders of magnitude larger than predicted by the L X − L B relationship in Fig. 6 of Matsumoto et al (1997). We assumed the halo luminosity given in Sect.…”
Section: The X-ray Halomentioning
confidence: 93%
“…Many ASCA studies found significant subsolar values for the iron abundance in groups and elliptical galaxies (e.g. Davis et al 1999;Matsumoto et al 1997), generally less than the stellar values in these systems and less than those observed in galaxy clusters. Buote (2000b) demonstrated that this was a bias resulting from fitting with a simple single-temperature a multi-temperature plasma, resulting in best-fitting elemental abundances that are too low.…”
Section: Introductionmentioning
confidence: 94%